2015 IEEE/ACIS 14th International Conference on Computer and Information Science (ICIS) 2015
DOI: 10.1109/icis.2015.7166658
|View full text |Cite
|
Sign up to set email alerts
|

Visualization in media big data analysis

Abstract: Nowadays the application of visualization technology is very wide while big data technology is rapidly developing. Data visualization can show the results of data analysis in an intuitive way, which has a very important practical significance. This paper studies a variety of media data visualization methods along with the development of media information. First of all, we introduce main basic contents and methods of text visualization; secondly, we introduce micro-blog data visualization capabilities and appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 1 publication
(1 reference statement)
0
8
0
Order By: Relevance
“…Qi Y et al studied the visualization method of media data combined with the media information and introduces text visualization and visualization method by using geographic information [5] . Chien-Tung Ho et al designed system to show the propagation path and social graph through analyzing the degree of propagation [6] .…”
Section: Correlated Visualization Methodsmentioning
confidence: 99%
“…Qi Y et al studied the visualization method of media data combined with the media information and introduces text visualization and visualization method by using geographic information [5] . Chien-Tung Ho et al designed system to show the propagation path and social graph through analyzing the degree of propagation [6] .…”
Section: Correlated Visualization Methodsmentioning
confidence: 99%
“…Visualization was also used to obtain pattern results indicated that the spread of Dengue disease occurred on periods [6]. Furthermore, [7] provided a summary research about text visual basic framework in big data analysis with three main parts: producing visualization of the process of text analysis, visual presentation, and interaction between user and text information. One of their most referenced research is from [8], which described the basic process visualization system for text analysis and understanding of the text as shown Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays the application of visualization technology is very widely used [7]. Available data visualizing tools in a free and open source system, such as D3.js and infoVis [17], motivate us to develop a visualization system that serves as a convenient tool for such a purpose.…”
Section: Introductionmentioning
confidence: 99%
“…It offers a visual system for humans to understand and explore the dataset. Visualization technology, originated from scientific computational visualization that appeared in the 1980s, assists individuals to observe, browse, discriminate, and understand information [13]. Visualization becomes both an art and a science that generate images or/and visual representations from large datasets [10,3,13].…”
Section: Introductionmentioning
confidence: 99%